Longitudinal Follow-Up of Long-Term Care Planning Using PlanYourLifespan.org. (May 2021) - Ramirez-Zohfeld, Vanessa; Seltzer, Anne; Ramirez, Ana; Muhammad, Ruqayyah; Lindquist, Lee A.
Many older adults wish to age-in-place but do not have long-term care plans for when they may require more assistance.PlanYourLifespan.org (PYL) is an evidence-based tool that helps older adults understand and plan for their long-term care needs. We examined the long-term effects of PYL use on user perceptions and planning of long-term care services. Individuals who previously accessed PYL were invited to complete an online, nation-wide mixed methodology survey about end-user outcomes related to PYL. Among 115 completed surveys, users found PYL helpful with long-term planning for their future needs. Over half of website users reported having conversations with others because of PYL use. However, 40% of respondents reported not having a conversation with others about their plans; common themes for barriers to planning included procrastination and a lack of immediate support needs. Although PYL helps with planning, many people are still not communicating their long-term care plans.